Pengaruh Pengetahuan Terhadap Minat Berinvestasi di Pasar Modal Syariah Pada Mahasiswa Fakultas Keislaman Universitas Trunojoyo Madura dengan Kemajuan Teknologi sebagai Variabel Mediating - Yulfika Yulfika; Dahruji Dahruji (Journal of Creative Student Research, 2023)
The Islamic Investment Gallery is a means of introducing Islamic Capital Market Investment to the world of academia and as a place to study investment and make investment transactions in the Islamic capital market. One of the causes of failure in investing is a lack of understanding in investing. Apart from knowledge, another factor in increasing interest in investing is technological advances as a medium in its activities. Therefore, this study aims to analyze the effect of knowledge on interest in investing in the Islamic capital market with technological advances as a mediating variable. This research is a quantitative research. Using the path analysis method in SPSS V.20. The results of this study indicate that knowledge has a direct effect on interest in investing in the Islamic capital market, knowledge influences technological progress as a mediating variable in interest in investing in the Islamic capital market, technological advances influences interest in investing in the Islamic capital market and knowledge influences interest in investing in Islamic capital markets. Through technological advances.